Inbreeding depression of sperm traits in the zebra finch Taeniopygia guttata - Opatová, Pavlína; Ihle, Malika; Albrechtová, Jana; Tomášek, Oldřich; Kempenaers, Bart; Forstmeier, Wolfgang; Albrecht, Tomáš (Ecology and evolution, 2016)
Inbreeding depression, or the reduction in fitness due to mating between close relatives, is a key issue in biology today. Inbreeding negatively affects many fitness-related traits, including survival and reproductive success. Despite this, very few studies have quantified the effects of inbreeding on vertebrate gamete traits under controlled breeding conditions using a full-sib mating approach. Here, we provide comprehensive evidence for the negative effect of inbreeding on sperm traits in a bird, the zebra finch Taeniopygia guttata. We compared sperm characteristics of both inbred (pedigree F = 0.25) and outbred (pedigree F = 0) individuals from two captive populations, one domesticated and one recently wild-derived, raised under standardized conditions. As normal spermatozoa morphology did not differ consistently between inbred and outbred individuals, our study confirms the hypothesis that sperm morphology is not particularly susceptible to inbreeding depression. Inbreeding did, however, lead to significantly lower sperm motility and a substantially higher percentage of abnormal spermatozoa in ejaculate. These results were consistent across both study populations, confirming the generality and reliability of our findings.
Keywords: Gamete performance; sperm velocity; genetic quality; sperm morphology; sperm abnormality